2016
DOI: 10.3109/02656736.2016.1164905
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous microwave ablation of adrenal tumours under ultrasound guidance in 33 patients with 35 tumours: A single-centre experience

Abstract: Percutaneous MWA under US guidance is effective in terms of good local control of adrenal tumours with a diameter of less than or equal to 5 cm and is capable of treating biochemically active tumours harbouring clinical syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…This rate is comparable to the rates reported in previous studies that used microwave (15.2%) and radiofrequency (23%) ablation. [1,16] Here, the median time to local progression was 17 months, which was within the range reported in prior studies that employed microwave (24 months) and radiofrequency (8.6 months) ablation. [1,16] These results may indicate that cryoablation has a similar effect in local control of adrenal metastases to the thermal ablation methods.…”
Section: Discussionsupporting
confidence: 80%
“…This rate is comparable to the rates reported in previous studies that used microwave (15.2%) and radiofrequency (23%) ablation. [1,16] Here, the median time to local progression was 17 months, which was within the range reported in prior studies that employed microwave (24 months) and radiofrequency (8.6 months) ablation. [1,16] These results may indicate that cryoablation has a similar effect in local control of adrenal metastases to the thermal ablation methods.…”
Section: Discussionsupporting
confidence: 80%
“…In response to the applied electrical field of microwaves, the rotation of dipole molecules and ionic polarisation produce friction and heat, thus inducing cellular death via coagulation necrosis [15]. This technology has been widely used to treat solid tumours of the liver, spleen, thyroid and other organs [16][17][18][19][20][21][22][23][24]. In 2011, Zhang et al [5] studied PMWA therapy for uterine fibroids and confirmed its safety and efficacy.…”
Section: Discussionmentioning
confidence: 99%
“… 29 2016 31 Retrospective Microwave ablation 77.4% NR by grade Ren et al. 30 2016 20 Retrospective Microwave ablation 84.8% None by SIR Frenk et al. 31 2017 38 Retrospective Radiofrequency, cryoablation, or microwave ablation 1 y 82% 2 y 75% Minor: 6% Major: 12% Botsa et al.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 Percutaneous ablative procedures such as microwave and radiofrequency ablation are also frequently used, and several retrospective series have reported 3-year OS rates >50%. 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 A noninvasive, ablative modality called stereotactic body radiation therapy (SBRT; also referred to as stereotactic ablative radiation therapy) has emerged as a promising alternative option for the local treatment of oligometastatic disease. 33 , 34 , 35 Preliminary experience with the use of SBRT to treat adrenal metastases demonstrates low toxicity rates with local disease control that ranges between 55% and 95% at 1 year.…”
Section: Introductionmentioning
confidence: 99%